2011
DOI: 10.1172/jci43586
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous challenge of orally immunized mice redirects antigen-specific gut-homing T cells to the skin

Abstract: Patients with atopic dermatitis (AD) often suffer from food allergy and develop flares upon skin contact with food allergens. However, it is unclear whether T cells sensitized to allergens in the gut promote this skin inflammation. To address this question, we orally immunized WT mice and mice lacking the skin-homing chemokine receptor Ccr4 (Ccr4 -/-mice) with OVA and then challenged them epicutaneously with antigen. Allergic skin inflammation developed in the WT mice but not in the mutants and was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 33 publications
(37 reference statements)
5
61
0
4
Order By: Relevance
“…[17][18][19] Flg ft/ft mice have attenuated profilaggrin expression in the epidermis and absent functional filaggrin monomer (see Fig E2 in this article's Online Repository at www.jacionline.org), which is similar to what is seen in FLG-null patients. 5 As neonates, Flg ft/ft mice spontaneously have marked ichthyosis-like dermatitis with edema, erythema, hyperlinearity, and scaling compared with WT control animals (Fig 1, A and B).…”
Section: Filaggrin Deficiency Leads To Spontaneous Dermatitis and Atopysupporting
confidence: 62%
“…[17][18][19] Flg ft/ft mice have attenuated profilaggrin expression in the epidermis and absent functional filaggrin monomer (see Fig E2 in this article's Online Repository at www.jacionline.org), which is similar to what is seen in FLG-null patients. 5 As neonates, Flg ft/ft mice spontaneously have marked ichthyosis-like dermatitis with edema, erythema, hyperlinearity, and scaling compared with WT control animals (Fig 1, A and B).…”
Section: Filaggrin Deficiency Leads To Spontaneous Dermatitis and Atopysupporting
confidence: 62%
“…Since the seminal work of the McLean Lab has underscored the importance of skin barrier abnormalities as an etiological factor in AD, we focused on the effects of coal tar on the epidermal biology of this disease (1, 3, 8). Our results reveal a key role of the AHR signaling pathway in breaching the vicious The immunopathogenesis of AD has been studied directly on patients or in animal models based on allergic immune responses (29)(30)(31). We have recently developed in vitro organotypic models for psoriasis and AD (18,19), and have shown that the application of genetic techniques in these models could be used to study epidermal aspects of diseases (32).…”
Section: Figurementioning
confidence: 91%
“…6 We used this model to investigate whether a robust IgE antibody is sufficient for oral anaphylaxis. WT BALB/c mice were orally immunized with OVA+CT or CT alone, as a negative control, by weekly gavage for 8 weeks, then orally challenged with OVA (Fig.…”
Section: Oral Immunization With Ova+ct Does Not Results In Anaphylaxismentioning
confidence: 99%
“…6,45 We previously reported that mechanical injury caused by tape stripping induces TSLP production in the skin, and that DCs derived from skin injured by tape stripping are programmed by TSLP to drive a Th2 response and migrate to MLN. 46 TSLP levels were elevated levels in EC sensitized skin (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation